2010
DOI: 10.1590/s1980-57642010dn40300014
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the use of rivastigmine transdermal patch in Alzheimer's dementia in a routine clinical setting

Abstract: There is not much published literature on the use of rivastigmine patch in a “routine” clinical setting.ObjectivesIn this naturalistic longitudinal observational study we sought to evaluate the safety, tolerability and efficacy of the rivastigmine patch in patients with early and late onset moderate Alzheimer’s disease in a routine clinical setting.MethodsOut of all routine clinical referrals, the first 30 patients with diagnosis of moderate Alzheimer’s dementia who were started on rivastigmine patch were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“… 41 However, only one study analyzing its application in AD patients was identified. 42 The BADL was used in studies of dementia patients 43 , 44 but no studies on its adaptation or validation for use in the Brazilian population were available.…”
Section: Functional Assessmentmentioning
confidence: 99%
“… 41 However, only one study analyzing its application in AD patients was identified. 42 The BADL was used in studies of dementia patients 43 , 44 but no studies on its adaptation or validation for use in the Brazilian population were available.…”
Section: Functional Assessmentmentioning
confidence: 99%